UTILIZATION OF SOIL MULCH FOR INCREASING SURFACE IRRIGATION PERFORMANCE AND WATER PRODUCTIVITY - Harby MOSTAFA; Mohamed ALI; Mohamed EL ANSARY (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Maximizing water productivity is one of the most important strategies in arid and semi-arid regions. Therefore, the aim of this study was to investigate the using of plastic mulch at field scale for improving the performance of surface irrigation in contrast to conventional practices in irrigated agriculture. The experiment was laid out in furrow and border irrigation system with three main treatments namely non-mulched furrows (NMF) (as control), plastic mulched furrows (FM) and plastic mulched-hole border (MB), and the sub main treatments were three lengths (15, 30 and 40 m). Each of the three main plots consisted of 9 irrigation parts each three of them represent one of the sub main treatments (furrow and border lengths). The spacing was 0.7m between all treatments. Squash crop was planted in April for two successive seasons. The results indicated that applied water was low in case of MB where the mulch effect reduced the number of irrigation times to the half. The maximum total yield was obtained from treatment with 30m length under MB (31.89 t/ha) followed by 15 m under MB (30.46 t/ha). As regard different irrigation practices with plastic mulch, maximum irrigation water productivity (8.33 to 9.15 kg/m3) was measured in MB for all lengths, followed by MF (5.11 to 5.41 kg/m2). The water saving was thus 10.44% and 46.3% under treatments MF and MB, respectively, when compared to NMF. The result of this study indicates that, using hole-mulching resulted a corresponding increasing of water productivity and water saving.